Effect Of Profitability, Leverage, Dividend Policy, And Investment Opportunity Set Value Company (Study of Banking Companies Listed on the Indonesia Stock Exchange in 2017-2020) - Annisa Windie Widyawati; Subadriyah Subadriyah (Jurnal Rekognisi Akuntansi, 2022)
This study entitled The Effect of Profitability, Leverage, Dividend Policy, and Investment Opportunity Set on Firm Value (Study on Banking Companies Listed on the Indonesia Stock Exchange in 2017-2020). And Investment Opportunity Set Against Company Value. This research is quantitative by using secondary time series data. The data collection technique in this study used purposive sampling method. Processing data in this study using Microsoft Excel and SPSS program. Data analysis techniques in this study using multiple linear regression analysis techniques, classical assumption test, hypothesis testing and descriptive statistics. The results of this study show that the variables of Profitability, Dividend Policy and Investment Opportunity Set have an effect on Firm Value, while the Leverage variable has no significant effect on Firm Value.